Analysis of Breach of Contract Agreement in a Company and Handling of Violations (Case Study on PT. Indo Rice Unggul) - Christy Giana Paath (IHSA Institute, 2025)
The violation of the agreement committed by PT. Indo Beras Unggul with Indomaret has violated article 1335 concerning an act by which one or more persons bind themselves to one or more persons. This journal was created with the aim of creating justice in contractual agreements and bringing optimal welfare. This research method uses the Qualitative Research Method and uses the analysis techniques of Literature Studies and Literature Studies, using data collection techniques based on the internet, books, journals, papers, and also articles. Based on the case raised by the author in this journal, it shows that both in terms of criminal law, especially in terms of civil law, that PT. Indo Beras Unggul violates article 1335 of the Civil Code which prohibits the making of contracts without causa, or made based on false or prohibited causa, with the consequence that it has no force. Because the rice provided by PT. indo Superior Rice to Indomaret is not in accordance with what was previously agreed. Therefore, the sanctions that can be given to PT. Indo Beras Unggul in accordance with the provisions of the Civil Code in article 1243 of the Civil Code regarding forced fulfillment, articles 1365 and 1367 of the Civil Code regarding compensation, articles 1266 and 1267 of the Civil Code regarding termination or cancellation of contracts, article 1253 of the Civil Code regarding the obligation to return. Therefore, the perpetrators must be given strict action regarding what has been done in accordance with the regulations and sanctions that have been set by the Law